Respiratory activity as vigor test in bean (Phaseolus vulgaris L.) seeds / Atividade respiratória como teste de vigor em sementes de feijão (Phaseolus vulgaris L.) - Caroline Marques Rodrigues; Edilma Pereira Gonçalves; Júlio César de Almeida Silva; Jeandson Silva Viana; Leandro Dias de Lima; Débora Teresa da Rocha Gomes Ferreira de Almeida (Universidade Estadual de Alagoas, 2019)
Rapid vigor tests are currently used by seed companies to evaluate batch quality. The seed industry with the technological evolution, demands faster and faster separation of high vigor lots. Thus, this work aimed to verify the efficiency and speed of seed respiratory activity to differentiate the vigor of bean seed lots. The work was carried out at the Rural University of Pernambuco, conducted at the Seed Analysis Laboratory with three bean lots acquired in municipalities of the state of Pernambuco. Some tests and determinations were performed: moisture content, one thousand seed weight, germination, first germination count, shoot and root length and dry mass, electrical conductivity, seedling emergence, shoot, root and dry mass length aerial part. The emergence speed index indicated lot 3 and 1 as the ones with the highest physiological potential and lot 2 as the lowest. Bean seeds from lot 2, in the germination tests, germination speed index, emergence speed index, shoot and root dry mass as the least vigorous lot, and which had the lowest CO2 release in the respiratory activity test. The respiratory activity test can be used to determine bean seed vigor after 12 hours of soaking.